Implementation of the 2013 Curriculum with a Scientific Approach in the Learning Process - Septiana, Monika; Hindun, Hindun (Journal Analytica Islamica, 2024)
This research aims to provide deeper insight into how the implementation of the 2013 Curriculum with a scientific approach is carried out at RA As-Sunbulah. This research used qualitative methods and was conducted at RA As-Sunbulah. The data collection techniques used in this research were interviews and documentation. The results of this research are that RA As-Sunbulah is one of the schools that has successfully implemented the 2013 Curriculum with a scientific approach. At RA As-Sunbulah, a scientific approach is implemented every day through a series of activities, starting from the introduction, core activities, to closing. By using this approach, RA As-Sunbulah not only focuses on developing students' intellectual aspects, but also emphasizes developing students' social, moral, spiritual and thinking skills. The aim is to shape students into individuals who are independent, creative, and able to face various challenges in everyday life. Penelitian ini bertujuan untuk memberikan wawasan yang lebih mendalam tentang bagaimana implementasi Kurikulum 2013 dengan pendekatan saintifik dilakukan di RA As-Sunbulah. Penelitian ini menggunakan metode kualitatif dan dilakukan di RA As-Sunbulah. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah wawancara dan dokumentasi. Hasil Penelitian ini yaitu RA As-Sunbulah adalah salah satu sekolah yang telah berhasil menerapkan Kurikulum 2013 dengan pendekatan saintifik. Di RA As-Sunbulah, pendekatan saintifik diimplementasikan setiap hari melalui serangkaian kegiatan, mulai dari pendahuluan, kegiatan inti, hingga penutup. Dengan menggunakan pendekatan ini, RA As-Sunbulah tidak hanya berfokus pada pengembangan aspek intelektual siswa, tetapi juga menekankan pada pengembangan sosial, moral, spiritual, dan keterampilan berpikir siswa. Tujuannya adalah untuk membentuk siswa menjadi individu yang mandiri, kreatif, dan mampu menghadapi berbagai tantangan dalam kehidupan sehari-hari.